2020
DOI: 10.1016/j.cell.2020.05.049
|View full text |Cite
|
Sign up to set email alerts
|

TBL1XR1 Mutations Drive Extranodal Lymphoma by Inducing a Pro-tumorigenic Memory Fate

Abstract: Highlights d TBL1XR1 mutation skews the humoral immune response toward producing memory B cells d TBL1XR1 mutant memory cells feature aberrant cyclic reentry to new germinal centers d Mutant TBL1XR1 acts by triggering aberrant targeting of SMRT complex to BACH2 d TBL1XR1 mutation gives rise to extranodal ABC-DLBCLs derived from memory B cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 114 publications
3
78
0
Order By: Relevance
“…This process may also be relevant to the MCD/cluster 5 subtype of DLBCL (defined based on co-occurence of Myd88 L265P and Cd79b mutations), which has extensive extra-nodal involvement and has one of the lowest survival rates of DLBCL subtypes 134,135 . MBCs were recently found to promote the progression of MCD/cluster 5 DLBCL 136 . A more precise understanding of the pathways that regulate MBC development and survival could offer new opportunities for the design of therapeutics capable of limiting follicular lymphoma and MCD-DLBCL progression.…”
Section: Concluding Remarks and Perspectivementioning
confidence: 99%
“…This process may also be relevant to the MCD/cluster 5 subtype of DLBCL (defined based on co-occurence of Myd88 L265P and Cd79b mutations), which has extensive extra-nodal involvement and has one of the lowest survival rates of DLBCL subtypes 134,135 . MBCs were recently found to promote the progression of MCD/cluster 5 DLBCL 136 . A more precise understanding of the pathways that regulate MBC development and survival could offer new opportunities for the design of therapeutics capable of limiting follicular lymphoma and MCD-DLBCL progression.…”
Section: Concluding Remarks and Perspectivementioning
confidence: 99%
“…Such findings suggest that FL may develop in a stepwise manner, from an ancestral MB-like premalignant progenitor that at an ulterior point becomes locked into a GCB profile (Figure 1b). Further supporting this model, we found that MCD/C5, a class of post-GC DLBCLs with unfavorable clinical outcomes (Chapuy et al 2018, Schmitz et al 2018, also arises through GC reentry (Venturutti et al 2020). In particular, lossof-function (LOF) mutations in TBL1XR1, a subunit of the SMRT/NCOR corepressor complexes central to the GCB program (discussed below), skew GCB cell fate towards an aberrant non-class-switched MB population with increased GC reentry capacity (Venturutti et al 2020).…”
Section: Germinal Center Reentry As a Prominent Lymphomagenesis Mechamentioning
confidence: 59%
“…The mutations primarily alter amino acids on the surface of the WD40 barrel structure that are predicted to have a role in protein-protein interactions. Venturutti et al 14 recently modeled these mutations using Tbl1xr1-cKO mice and mice with conditional knock-in of a Tbl1xr1 D370Y mutant allele (Tbl1xr1-D370Y). Using a GCBspecific Cre allele, homozygous cKO and heterozygous Tbl1xr1-D370Y knock-ins were found to have significantly reduced frequencies of GCB cells and smaller GCs after immunization.…”
Section: C5/mcd Subtype Of Dlbcl: Getting In On the Actionmentioning
confidence: 99%
“…7 Therefore, understanding the epigenetic basis for lymphoma is an important challenge due to the high potential for clinical translation that could improve patient outcomes. Here, we discuss recently published (2018-2020) studies [8][9][10][11][12][13][14] and their translational implications.…”
Section: Introductionmentioning
confidence: 99%